NEGOTIATION SKILLS AS A KEY COMPETENCY OF A MODERN ENTREPRENEUR: CASE OF UZBEKISTAN (The Journal of Interdisciplinary Human Studies, 2026)
The primary objective of this study is to investigate the role of negotiation skills and competencies in fostering conducive working conditions in culturally diverse business environments of Uzbekistan. This qualitative research employs semi-structured interviews with 15 entrepreneurs owning their businesses in Tashkent to examine the level of these competencies, highlight possible challenges they face, and outline the areas for improvement. The findings offer important insights into conflict and negotiation at workplace. They demonstrate that the entrepreneurs’ demographic data, as well as their educational background and work experience, influence the application of specific negotiation and conflict resolution techniques that contribute to a more positive work environment in Uzbekistan’s diverse business context.
Keywords: negotiation skills; interpersonal skills; conflict management; entrepreneur; Uzbekistan